Nestin Expression Affects Resistance to Chemotherapy and Clinical Outcome in Small Cell Lung Cancer - Sone, Kazuki; Maeno, Ken; Masaki, Ayako; Kunii, Eiji; Takakuwa, Osamu; Kagawa, Yusuke; Takeuchi, Akira; Fukuda, Satoshi; Uemura, Takehiro; Fukumitsu, Kensuke; Kanemitsu, Yoshihiro; Ohkubo, Hirotsugu; et al. (Frontiers in Oncology, 2020)
OBJECTIVES: Small cell lung cancer (SCLC) is an aggressive and highly metastatic lung cancer subtype. Nestin is a member of the intermediate filament family and serves as a potential proliferative and multipotency marker in neural progenitor and stem cells. Aberrant expression of nestin is linked to poor prognosis in different cancers, including non-small cell lung cancer. However, the association between nestin expression and clinicopathological feature or prognosis has remained unclear for SCLC. This study examined whether nestin expression was associated with malignant features and clinical outcomes in SCLC. MATERIALS AND METHODS: Using previously established Nestin knock-down cells and a newly established Nestin-overexpressing cell line, we examined the relationship between nestin expression and cell proliferation in vitro and in vivo and chemosensitivity. We also analyzed nestin expression in three drug-resistant lung cancer cell lines. Furthermore, we examined samples from 84 SCLC patients (16 patients with surgical resection, and 68 patients with biopsy), and immunohistochemically analyzed nestin expression. RESULTS: Nestin expression correlated positively with cell proliferation, but negatively with chemosensitivity. Nestin expression in drug-resistant cell lines was upregulated compared to their parental cells. Among the 84 SCLC patients, 24 patients (28.6%) showed nestin-positive tumor. Nestin-positive ratio tended to be higher in operated patients than in biopsied patients. Nestin-positive and -negative patients showed no significant differences in response rate (RR) or progression-free survival (PFS) following first-line chemotherapy. However, positive expression of nestin was associated with shorter PFS following second-line chemotherapy (median PFS: nestin-positive, 81 days vs nestin-negative, 117 days; P=0.029). CONCLUSIONS: Nestin expression may be associated with malignant phenotype and worse outcome in SCLC patients.